The Communist Manifesto: What can we learn today for a country like Vietnam? - Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
Today we can learn from the Communist Manifesto that unregulated markets lead to disastrous economic, social, and political developments, which can endanger the reproduction of the capital system itself. The liberal argument, based on Adam Smith's invisible hand - that markets coordinate the selfish actions of millions of people and lead to the welfare of nations -, is a dangerous dream. The consequence is that politicians should not listen to economists, including foreign advisors who preach the liberal dreams of radical versions of capitalist systems. Especially for developing countries, it is vital that they strive for a regulated version of capitalist development. Marx and Engels had a deep understanding of the functioning of capitalism. They underestimated the possibilities to regulate the capitalist system and also allowed the working class to take part in prosperity. However, there is always the danger that capitalist systems evolve with low levels of regulation with the features of capitalism analysed in the Manifesto.
Keywords: B14; B30; O11; 330; Marxism; Communist Manifesto; capitalism; development strategy